Effects of corneal epithelial remodeling on corneal asphericity after FS-LASIK and Trans-PRK: A prospective study - Mingyu Xu; Fan Yang; Emmanuel Eric Pazo; Qiwei Li; Zheng Yang; Yue Huang; Shaozhen Zhao (Indian Journal of Ophthalmology)
Purpose: To observe the changes in corneal epithelial thickness after FS-LASIK and Trans-PRK surgery and to investigate the impact of corneal epithelial remodeling on Q-value and HOA. Methods: In this prospective cohort study, 50 patients (100 eyes) underwent FS-LASIK and 45 patients (90 eyes) underwent Trans-PRK. Anterior segment OCT was used to measure the corneal epithelial thickness in different corneal zones (central zone: 0–2 mm; paracentral zone: 2–5 mm; and mid-peripheral zone: 5–6 mm) preoperatively and postoperatively at 1 week, 1 month, 3 months, and 6 months. The correlation between △CET in the superior, nasal, inferior, and temporal region at 6 months postoperatively and △Q and △HOA was analyzed. Results: At 6 months postoperatively, the epithelial thickness increased in the central, paracentral, and mid-peripheral zones in FS-LASIK and Trans-PRK. Central epithelial thickness and different regions of the paracentral zone and mid-peripheral exhibited significant thickening (P < 0.001). In the para-central zone and mid-peripheral zone, the △CET in different regions after LASIK and Trans-PRK was positively correlated with △Q (P < 0.05) and △HOA (P < 0.05). Conclusion: After FS-LASIK and Trans-PRK, significant epithelial thickening was observed. Epithelial changes in different regions lead to different Q-values in different regions and have different effects on HOA. This has a certain guiding significance for the design of refractive surgery, and minimizing the increase of Q-value may improve the postoperative visual quality.